“Clan Crime” in Germany: Migration Politics, Socio-Economic Conditions, and Intergenerational Transmission of Criminal Behavior - Jaraba, Mahmoud (Organized Crime in the 21st Century, 2023)
In Germany, an intense political and media discussion has emerged on the phenomenon of “clan crime” (Clan-Kriminalität). In the course of the debate, “Arab clans” have often been accused of establishing criminal networks based on kinship and family ties. Despite the public debate, however, there has been a very little empirical research on the topic and virtually no attempt to understand it on a scientific basis by examining its socio-historical and cultural contexts. In this chapter, I demonstrate the roles of migration politics, socio-economic conditions, and kinship dynamics in shaping the structure and character of “clan crimes” in Germany. I argue that when a crime is committed by the member of a clan, it usually takes place either within that person’s nuclear family or independently of it and not at a clan level. Despite a widespread belief to the contrary, in my fieldwork, I found no evidence of clans either organizing or supporting organized criminal activity. <br
Keywords: Clan crime; Migration politics; Socio-economic conditions; Intergenerational transmission of criminal behavior; Marginalization and exclusion; Mhallami